Expression of Bax Protein as A Prognosis Factor of Radiotherapy Response to Decreased Tumor Size in Stage IIB-IIIB Cervical Cancer - Fitriawan, Ahmad; Udiyanto, Hermawan; Respati, Supriyadi Hari; Ratnasari, Affi Angelia; Prabowo, Wisnu (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Cervical cancer plays a role as the leading cause of cancer death for women in developing countries. Radiation therapy kills cancer cells through double strand breaks and the apoptotic process. Bax protein is one of the regulators of apoptosis. This study analyzed the role of Bax expression as a prognostic factor in radiation therapy response in reducing tumor size in patients with advanced cervical cancer (IIB-IIIB). Subjects and Method: This research is a retrospective cohort observational analytic study from January 2021 to April 2021 in the Department of Obstetrics and Gynecology in collaboration with the Department of Anatomical Pathology, Dr. Moewardi Hospital, Surakarta, Indonesia. This study involved 30 cervical cancer stage IIB-IIIB patients. The level of Bax expression was determined by immunohistochemical examination. ROC curve analysis was used to find cut-off points and evaluate the sensitivity and specificity of Bax in the prognosis of radiotherapy in patients with advanced cervical cancer (IIB-IIIB). Chi square test was used to determine the relationship between Bax expression and changes in tumor size in cervical cancer patients. Results: The ROC curve analysis showed that the AUC Bax score in prognosis of radiation therapy was 0.575 (CI 95%= 0.32 to 0.83) and the cutoff point was 62.5%. Based on the analysis of the ROC curve, the Bax expression of 62.5% shows a sensitivity of 56.5% and a specificity of 71.4%. Analysis of the relationship between Bax protein expression on changes in tumor size using the Chi Square test showed a P value of 0.390 (p> 0.05). Conclusion: The expression of Bax protein cannot play a role as a prognostic factor in the response of radiation therapy to the reduction in tumor size in stage IIB-IIIB uterine cervical cancer.